2008
DOI: 10.1007/s11325-008-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and history of asthma in snoring children

Abstract: Asthma has been identified as a possible risk factor for Obstructive Sleep Apnea (OSA) in children. It is not known whether parent-reported asthma increases the likelihood of the diagnosis of OSA in snoring children. We hypothesized that snoring children with asthma are more likely to have OSA than snoring children without asthma. This study is a 1-year retrospective review of polysomnogram and questionnaire data collected on 236 patients referred to the University of Maryland Pediatric Sleep laboratory for ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
1
29
2
3
Order By: Relevance
“…3 Means of annualized medical cost by cohort and by diagnosed sleep apnea syndrome. Predictions adjusted for age, gender, race, obesity, Charlson Comorbidity Index, and days in cohort between SAS and asthma has been suggested by some [9,19], in children, Ramagopal et al [20] found that asthma was actually a negative predictor of SAS. In our sample of middle-aged adults, there are three other possible explanations for the low prevalence of SAS among beneficiaries with asthma.…”
Section: Discussionmentioning
confidence: 93%
“…3 Means of annualized medical cost by cohort and by diagnosed sleep apnea syndrome. Predictions adjusted for age, gender, race, obesity, Charlson Comorbidity Index, and days in cohort between SAS and asthma has been suggested by some [9,19], in children, Ramagopal et al [20] found that asthma was actually a negative predictor of SAS. In our sample of middle-aged adults, there are three other possible explanations for the low prevalence of SAS among beneficiaries with asthma.…”
Section: Discussionmentioning
confidence: 93%
“…The underlying mechanism for the obesity-asthma link remains controversial. Factors stemming from obesity including greater systemic inflammation (36)(37)(38)(39), gastro-esophageal reflux (40)(41)(42)(43), obstructive sleep apnea (44)(45)(46), and reduced lung volumes (47,48) 47;48 are all plausible mechanisms. In addition, it is unclear how accurately and consistently various physicians diagnose asthma (49).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma has been identified as a risk factor for childhood obstructive sleep apnea (OSA), which is more common in overweight children [27]. Overweight without sleepdisordered breathing is not associated with increased airway inflammation [28].…”
Section: Sleep-disordered Breathing In Asthmatic Children and Adenoidmentioning
confidence: 99%